ANALISIS LAPIS PERKERASAN TAMBAH DAN DRAINASE PADA RUAS JALAN WAEMITAL-KAWATU KABUPATEN SERAM BAGIAN BARAT - Pattiradjawane, Juan Devid; Metekohy, Selly; Johannes, Standy (Journal Agregate, 2023)
Handling road damage by overlaying the old road surface layer and planning a drainage system to improve the area value of the Waemital-Kawatu road section, West Seram Regency. The aim of the research was to determine the thickness of the overlay layer and the channel dimensions needed by the Waemital-Kawatu road section, West Seram Regency. The data used are primary data and secondary data then analyzed using the 2017 Road Pavement Design Manual Method for Additional Pavement Layers and the Rational Method for Drainage, then data processing is carried out referring to these regulations. Based on the results of this research, it was obtained that the CBR of class A aggregate foundation layer was 54%. So that with a design life of 20 years and a traffic value on the design lane of 801,068.59, the pavement layer thickness (overlay) with AC-WC = 40 mm, AC-BC layer thickness = 60 mm, class A aggregate layer thickness = 400 mm is obtained. . The results of the calculation of the drainage channel for a 5-year return period obtained a planned rainfall of 134,259 mm, with a population growth percentage of 1.1% per year so that the population of Waemital Village in 2026 is 7,443 people. From the results of the analysis of the drainage system, it was found that the planned discharge of the drainage channel on the Waemital-Kawatu Road Section was 0.0635 m3/sec, and the discharge of the drainage channel on the Waemital-Kawatu Road Section was 0.078197 m3/sec, then it was found that the discharge capacity of the channel was greater from the design discharge, so that the plan dimensions are declared safe.